A Constant Market Share Analysis of Indonesia's Fishery Export - Candra Aryudiawan; Suadi Suadi (Jurnal Perikanan Universitas Gadjah Mada, 2022)
Despite its importance in global fishery production as the world's second-largest producer, Indonesia is not one of the top ten fish exporting countries. This study uses constant market share analysis to examine Indonesia's fishery export performance. The data was collected from the United Nations International Trade Statistics Database and covered Indonesia's fishery exports from 1999 to 2019. Indonesian fishery products are classified using four-digit Harmonized System codes ranging from 0301 to 0308. Export growth is decomposed into four components: the global market, commodity compositions, market distributions, and competitiveness effects. The results indicate that the significant growth of the global fishery trade was the primary driver of Indonesia's fishery exports during the period. Indonesia is directing a significant portion of its exports to the most dynamic destination markets, such as China and ASEAN countries. The commodity composition and competitiveness effects were negative and significant throughout the period. Indonesia's integration into the global economy through structural adjustment programs, a liberalization strategy, WTO accession, and participation in several trade agreements, but these policies have had little impact on competitiveness. Indonesia's share of the global fish trade has declined from 4.11 percent in 1999 to 2.75 percent in 2019. Over the last 20 years, Indonesia's market share has gone down, which shows its lack of competitiveness.